IL‐33 induces Egr‐1‐dependent TSLP expression via the MAPK pathways in human keratinocytes. Issue 11 (21st August 2015) - Ryu, Woo‐In; Lee, Hana; Kim, Jin Hee; Bae, Hyun Cheol; Ryu, Hwa Jung; Son, Sang Wook
Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease in which T‐helper type 2 (Th2)‐type immune responses are dominant. Th2 cytokine, interleukin (IL)‐33 and thymic stromal lymphopoietin (TSLP) have been suggested to have an important role in AD. IL‐33 is highly expressed in AD, but its role in AD has not yet been fully understood. To further identify the role of IL‐33 in AD, we investigated the expression of TSLP induced by IL‐33 in keratinocytes. This study revealed that IL‐33 induced TSLP expression in human keratinocytes. Early growth response protein 1 (Egr)‐1, which is an inflammatory transcriptional factor, is induced by IL‐33. IL‐33‐mediated TSLP induction in keratinocytes was suppressed by treatment with mitogen‐activated protein kinase (MAPK) inhibitors or small interfering RNA against Egr‐1. Chromatin immunoprecipitation (ChIP) assay indicated the direct involvement of Egr‐1 in IL‐33‐mediated TSLP induction. Taken together, these findings indicate that IL‐33 may increase TSLP expression through an Egr‐1‐dependent mechanism via ERK1/2, JNK and p38 activation in keratinocytes. These data suggest that the IL‐33‐ERK/JNK/p38/Egr‐1/TSLP axis is involved in allergic skin Th2 inflammation, and it may be a novel therapeutic target.